Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-1211288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood Blood Lead Levels and Environmental Risk Factors in Madagascar

Abstract: One-third of children globally have blood lead levels (BLLs) exceeding the US CDC reference value of 5 µg/dL; this value may be as high as one-half for children in low- and middle-income countries (LMICs). Lead exposure occurs through a variety of routes (e.g., water, dust, air), and in LMICs specifically, informal economies (e.g., battery recycling) can drive lead exposures due in part to absent regulation. Previous work by our team identified a ubiquitous source of lead (Pb), in the form of Pb-containing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Prior studies in Toamasina have found that approximately one-third of the pitcher pumps with leaded components exhibit lead concentrations above the WHO provisional drinking water guideline of 10 µg/L (Buerck et al, 2021). In turn, exposure from cooking and drinking this water results in around 34% of children ages one to five with blood lead level (BLLs) concentrations of over 5 µg/dL, a level at which point irreversible health consequences occur (ACCLPP, 2012; Buerck et al, 2021; Champion et al, 2022; World Health Organization, 2010, 2019).…”
Section: Background and Situation Analysismentioning
confidence: 99%
“…Prior studies in Toamasina have found that approximately one-third of the pitcher pumps with leaded components exhibit lead concentrations above the WHO provisional drinking water guideline of 10 µg/L (Buerck et al, 2021). In turn, exposure from cooking and drinking this water results in around 34% of children ages one to five with blood lead level (BLLs) concentrations of over 5 µg/dL, a level at which point irreversible health consequences occur (ACCLPP, 2012; Buerck et al, 2021; Champion et al, 2022; World Health Organization, 2010, 2019).…”
Section: Background and Situation Analysismentioning
confidence: 99%